Peningkatan Hasil Belajar Melalui Metode Demonstrasi Materi Sujud Syukur, Sujud Sahwi dan Sujud Tilawah di Kelas VII A SMP Negeri 10 Kota Bengkulu - Efi Susanti (GHAITSA : Islamic Education Journal, 2023)
The application of the demonstration method is very important in learning Islamic Religious Education, especially those related to fiqh material such as thaharah, prayer, prostration and so on. The role of the demonstration method is to provide learning experiences through seeing and practicing so that students can easily imitate, understand and apply it in everyday life. This research is qualitative research in the form of Classroom Action Research which aims to improve learning outcomes regarding the material of prostration of gratitude, prostration of sahwi and prostration of recitations. The problem in this research is whether the use of this demonstration method can improve learning outcomes regarding prostration of gratitude, prostration of sahwi and prostration of recitations? The research subjects were 15 students who were in class VII A of SMP Negeri 10 Bengkulu City. This research was carried out in 2 cycles. Each cycle uses action procedures, namely planning, implementing actions, observing and reflecting. Data from the results of cycle 1 action show that the average student learning outcomes have increased with a class average of 71.5. Then the results of cycle 2 action show that the average ability of student learning outcomes has increased again, as seen from the class average value reaching 85.7 Based on the data from the results of the actions above, it can be concluded that the use of the demonstration method can improve student learning outcomes in the material of prostration of gratitude, prostration of sahwi and prostration of recitations in class VII A students of SMP Negeri 10 Bengkulu City, Semester I, Academic Year 2023/2024.